Pengolahan Minyak Jelantah Menggunakan Membran Poliamida/Titanium Dioksida/Arang Aktif Kulit Durian - Safitri, Rika Endara; Hayaati, Ria Sheftiana Rusli (Universitas Andalas, 2021)
Processing of wasted cooking oil uses the photocatalyst method with metal catalysts and zeolites to reduce organic compounds. In this study, researchers used activated charcoal from durian skin and titanium dioxide embedded in a polyamide membrane as an adsorbent which was used as a medium for processing wasted cooking oil. The purpose of this study was to determine the effect of processing used cooking oil using a membrane of polyamide/titanium dioxide/durian peels activated charcoal on changes in the characteristics of wasted cooking oil. Based on the results of research on the processing of wasted cooking oil with a membrane of polyamide/titanium dioxide/activated charcoal from durian peels, there was an increase in water content by 10.21%, a decrease in free fatty acids by 33.75%, a decrease in the peroxide number by 18.33%. Used cooking oil that has passed through the membrane has a decrease in %Transmission for the functional groups of C-H alkenes, C-O esters, and C-H alkanes. In the analysis of the compound content by mass spectrophotometry, it was found that the content of the methyl ester compound with the C17 and C19 chains was close to the composition of the biodiesel constituents.